Scanning laser ophthalmoscopy in an elderly Indian population. (2nd November 2018) - Srinivasan, Geetha; Murthy, Gudlavalleti Venkata Satyanarayana; Mohan, Shalini; Mani, Kalaivani; Vashist, Praveen; John, Nina; Gupta, Viney; Sihota, Ramanjit
ABSTRACT: Purpose : To study optic nerve head (ONH) characteristics using scanning laser ophthalmoscopy, Heidelberg retina tomograph (HRT), in an elderly population. Methods : A population-based, cross-sectional study included 1460 eyes of 1460 consecutive, subjects >60 years, in North India. All subjects underwent a detailed ophthalmic evaluation and imaged on HRT. Stereometric parameters, Moorfields regression analysis (MRA) and discriminant function analysis were analyzed. Correlation between ONH parameters and disc area, age, sex, and intraocular pressure was analyzed. Results : Disc size had a normal Gaussian distribution (2.22 ± 0.48 mm 2 ), but all other stereometric parameters showed a wide variation. MRA found 1320 (90.4%) eyes within normal limits, 71 (4.86%), borderline limits, and 69 (4.73%) outside normal limits. Comparison of eyes meeting International Society of Geographical and Epidemiological Ophthalmology criteria for a glaucoma suspect, C:D > 0.7, with those that did not show a statistically significant difference in the cup area, rim area, rim disc ratio, and cup volume ( p  = 0.02, 0.02, 0.02, 0.03, respectively). An Intraocular pressure (IOP) ≥21 mmHg was seen in 3.01%, and only 12 eyes out of 1460, 0.82%, had an IOP ≥21 mmHg and a cup:disc ratio of more than 0.7. A van Herick estimation of < Grade 3 was seen in 19.4% Conclusions : Stereometric parameter data, MRA, and clinical examination in this population at high risk for glaucoma found that about 10% of individuals over 60 years of age could be classified as glaucoma suspects and would need further evaluation.